POS Android untuk Transaksi Offline-Online di Bengkel Remaja Motor - Imanda, Ridho Novan; Listyorini, Tri; Supriyati, Endang (LPPM STIKOM Tunas Bangsa, 2025)
Bengkel Remaja Motor, a workshop that has been operating for more than 45 years, faces challenges in managing transactions due to its manual processes. These challenges include difficulties in checking spare part prices, issuing receipts, and the absence of digital payment options. This study focuses on the development of a digital cashier application designed for the Android platform. The application is tailored to meet the specific needs of end-users, featuring an offline mode for cash transactions and an online mode for digital payments. The system is built using Laravel for the backend and Flutter for the user interface, with Bluetooth Printer integration to enable receipt printing. The Rapid Application Development (RAD) approach, which emphasizes user feedback, was adopted to accelerate the development process. Testing results demonstrate that the system facilitates transaction management, supports digital payments via Midtrans, and operates effectively in both offline and online environments. This system is expected to enhance the operational efficiency of Bengkel Remaja Motor.